Barnperspektivet i handläggningen av ekonomiskt bistånd : "Vad är barnets bästa? Det är ju en tolkningsfråga" - Maltesson,Rebecca; Werkström,Karin (2020)
The aim of this thesis has been to analyze how social workers relate to the child perspective in the processing of social assistance. Previous studies have shown that there is a knowledge gap among social workers how to implement the child's perspective in the management of social assistance. This study has a qualitative research approach and six semi structured interviews have been conducted. Opportunities and limitations that can be identified with the work on the child perspective are addressed throughout the thesis. The empirical material has been analyzed based on Michael Lipsky´s theory about street-level bureaucracy and the key concepts that are illustrated are among others: lack of resources, power and discretion. Furthermore, the respondents illustrate the discretion as both a positive and a negative aspect. With their professional judgement they can decide how they want to distribute their work and find the most effective solution for the clients. Workload, lack of information, organizational guidelines and legislation may limit the discretion for the social workers. Social Services Act and The UN convention on the rights of the child are two central laws. Key concepts of the legislation are the best interest of the child followed by age and maturity. The result shows that social workers often form their own opinion regarding the meaning of the concepts, which is reflected in the work with the child perspective.
Keywords: Child perspective; social assistance; discretion; power; resources.